Network Management / Concept and Practice: A Hands-on Approach - Burke Richard (Pearson - Prentice Hall, 2004)
This textbook shows students and professionals how to implement network management concepts. Includes CD-ROM. Networking Components, Overview of Network Management, Network Implementation and Management Strategies, Configuration: Client/ Server Components, Configuration: Infrastructure Components, SNMP, Management Information Bse (MIB), Remote Monitoring (RNON1), RMON2, Desktop Management, Web-Based Management, SNMPv3, Desktop Management, IP Addressing and ARP and RARP, Abstract Syntax Notation 1 (ASN.1), Management Information Base for Network Management of TCP/ IP - bASED Internets MIB-II, Basic Encoding Rules (BER), Information Management Initiatives, Additional Meterware Tools, Acronyms, Glossary, Index.